Soil Nutrients in Sandy Plantations Are Related to the Species, Diameter at Breast Height or at Base, and Distance from the Tree Base in Horqin - Hongshun Liu; Rencang Bu; Yu Chang; Li Qi; Chang Chang; Zhibin Zhang; Lujia Zhao (Land)
Correctly understanding existing plantations and improving the cycles and effects of ecological restoration in sandy areas have become important scientific issues. Consequently, we selected different diameters at breast height (DBHs) for Populus spp. and Pinus sylvestris var. mongolica (P. sylvestris var. mongolica) and varying diameters at the base (DBs) of Caragana microphylla Lam. (C. microphylla) as research subjects in the sandy plantations in northwestern Liaoning Province. Soil samples were collected along a gradient at distances of 20 cm, 60 cm, and 120 cm from the tree base. Our objective was to investigate the connections among various afforestation species, DBHs or DBs (age), and soil nutrients. The results from our study area revealed that (1) the soil nutrient contents were extremely low; (2) the DBHs or DBs were not significantly related to soil exchangeable phosphorus (EP), total potassium (TK), or Pondus Hydrogenii (pH) but had a significant or moderately positive correlation with soil organic carbon (SOC), exchangeable potassium (EK), total nitrogen (TN), total carbon (TC), and total phosphorus (TP). The most significant relationship was with EK at a distance of 20 cm from the tree base; (3) the three afforestation species presented different trends in terms of the soil nutrient contents among the different distances from the tree base; and (4) the EK in the Populus spp. plantations was significantly greater than that in the P. sylvestris var. mongolica plantations and moderately significantly greater than that in the C. microphylla plantations. The pH levels in P. sylvestris var. mongolica plantations were significantly lower than those in Populus spp. plantations and C. microphylla plantations. Our study provides valuable insights into the synergistic development between sandy plantations and soil dynamics. This study provides important evidence for selecting suitable plant species for vegetation restoration and improvement efforts in sandy lands.